Dockums, detail model - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2022)
Right by the old Dock in Malmö, Region Skåne has got an office building. The new building was to interact with the surrounding buildings. These have a horizontal alignment in the facade expression and protrusions one the corners, which gives the building its direction and dynamism. To stabilize the "space", the new quarter has been designed with a more direction-neutral expression. The materials and colours were adapted from the surrounding. The slated outdoor floor has a pattern inspired by the facades' window installation. Between the slate slabs, there are wide joints with moss and sedum plants. The courtyard, which is located on the terrace floor, is a meeting place with standing tables and seats in the sun.